The efficiency of membrane anaerobic system (MAS) in treating sugarcane mill effluent (SCME) - Zaki, Yasmeen Hafiz; Nour, A. H.; Mohamed, Hybat Salih; R. M., Yunus (IOP Publishing, 2019)
In recent times, the environmental issues have been on an alarming rate mostly for public authorities, societies, and industrial establishments. Sugarcane mill effluent (SCME) which contain high miscellaneous pollutants such as the chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solid (TSS) and the volatile suspended solid (VSS). However, the conventional method has the merit of COD reduction from SCME, but is limited in capturing the methane gas produced. In this study the membrane anaerobic system (MAS) was used as a cost-effective replacement method for treating SCME. In this study, six steady states were reached as part of the kinetic study with concentration ranging from 6312 to 14043 mg/l. for the mixed liquor suspended solids (MLSS) and 4790 to 12887 mg/l for mixed liquor volatile suspended solids (MLVSS). The three kinetic equations (Monod, Contois and Chen and Hashimoto) were used to explain the kinetics of SCME treatment at organic loading rates ranging from 0.5 to 13 kg COD/m3/day. The removal efficiency of COD was from 94.2% to 93.9% and produced methane gas (CH4) 75.4%. The scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (SEM/EDX), and Fourier transforms infrared spectroscopy (FTIR) were subsequently used to quantitatively and qualitatively determine the content of the biomass before and after treatment.